Association between thyroid cancer of cribriform variant and familial adenomatous polyposis. Issue 7 (July 1996) - Hizawa, K; Iida, M; Yao, T; Aoyagi, K; Oohata, Y; Mibu, R; Yamasaki, K; Hirata, T; Fujishima, M
Abstract : A case of a 20 year old Japanese woman who developed thyroid cancer exhibiting unusual cribriform structures while being followed up for familial adenomatous polyposis/Gardner's syndrome is reported. The patient presented with osteomas, pigmented retinal lesions, and adenomas of the duodenum and the papilla of Vater, in addition to numerous adenomatous polyps in the colorectum. On ultrasonography, the thyroid cancer was localised to the right lobe and was identified as an irregular, internal echo tumour with a peripheral hypoechoic zone, measuring 1.8 cm in diameter. Histological examination of the resected tumour showed a concomitance of papillary proliferation and cribriform structures with follicles of varying sizes. These features can be distinguished from sporadic thyroid cancer.